PROSES PERENCANAAN PENGALIHAN PBB P2 SEBAGAI PAJAK DAERAH DI KABUPATEN TRENGGALEK - Edy Santoso; Abdul Juli Andi Gani; Tjahjanulin Domai (REFORMASI, 2015)
This research is motivated because the issuance of Law No. 28 of 2009 on Local Taxes and Levies, which the Central Government gives full authority to local governments to manage their own land and building tax Sector Rural and Urban Sector (PBB P2). The purpose of this study is to describe, interpret, and analyze (1) the transfer planning of PBB P2 in Trenggalek, (2) enabling factors and factors inhibiting the transfer of PBB P2 Areas in Trenggalek Local Goverment. The results of the study (1) goal setting plan made after seeing the condition of the existing and likely to happen, then think about what activities will be undertaken to achieve these objectives. The purpose or primary objectives guided Terri District Government Joint Regulation of the Minister of Finance and Minister of Home Affairs No. 213 / PMK.07 / 2010 - Number 58 Year 2010 concerning the transfer of the stages of preparation of the PBB P2 as Local Tax, with funding from the budget, and carried out by the Department of Revenue Trenggalek but this plan was not made official schedule. Broadly speaking, the implementation of the plan in accordance with the existing rules, but there are some who passed the deadline. Monitoring is difficult because of the absence of the official schedule. (2) Supporting factors of Trenggalek Local Goverment planning process is the availability of funds and good relationships with various stakeholders, while inhibiting factor is the Human Resources both of quality and quantity, the absence of an official schedule as well as the difference between the amount receivable.